2010
DOI: 10.1086/651452
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation ofMycobacterium tuberculosisFunctionally Disrupted in a Fatty Acyl–Coenzyme A Synthetase GenefadD5

Abstract: One key adaptation that Mycobacterium tuberculosis established to survive long term in vivo is a reliance on lipids as an energy source. M. tuberculosis H37Rv has 36 fadD genes annotated as putative fatty acyl-CoA synthetase genes, which encode enzymes that activate fatty acids for metabolism. One such gene, fadD5 (Rv0166), is located within the mce1 operon, a cluster of genes associated with M. tuberculosis persistence. We disrupted the putative fatty acid binding site of fadD5 in H37Rv M. tuberculosis. No si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 31 publications
2
74
0
Order By: Relevance
“…On the other hand, disruption of the other operons attenuates the mutants (Senaratne et al, 2008;Marjanovic et al, 2010). More recently, the mce1 operon was shown to be involved in fatty acid or mycolic acid importation (Dunphy et al, 2010), while mce4 was suggested to encode a cholesterol import system (Pandey and Sassetti, 2008). These observations support the idea that these operons are involved in bacterial and host lipid processing during infection.…”
mentioning
confidence: 64%
“…On the other hand, disruption of the other operons attenuates the mutants (Senaratne et al, 2008;Marjanovic et al, 2010). More recently, the mce1 operon was shown to be involved in fatty acid or mycolic acid importation (Dunphy et al, 2010), while mce4 was suggested to encode a cholesterol import system (Pandey and Sassetti, 2008). These observations support the idea that these operons are involved in bacterial and host lipid processing during infection.…”
mentioning
confidence: 64%
“…During this nutrient-limited state, M. tuberculosis may down-regulate the propionyl-CoA/ methylmalonyl-CoA pathway involved in the synthesis of SL-1, DAT, and PAT, while increasing the synthesis of MA, which has even lower pro-infl ammatory activity 8,30 . Dunphy et al 93 proposed that the mce1 operon is involved in MA import. A prolonged starvation of the cells with thickened cell wall may serve as a signal to de-repress the mce1 operon to allow the importation of FM, a carbon source.…”
Section: Lipid Synthesis Control and A Bacterial Immunostatmentioning
confidence: 99%
“…Originally thought to be simply involved in gaining entry to host cells, 3 more recent work 9 suggests that the Mce1 protein complex is also involved in the recycling of extracellular mycolic acids for use as a carbon source. Of particular interest, we show that the genes that were significantly upregulated by the macrophages in the period immediately after infection by M. tuberculosis H37Rv, but not D-mce1 H37Rv, were primarily involved in substrate trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, more recent studies show that the mce operons encode for lipid uptake transporters 8 and that the mce1 operon is involved in fatty acid transport/metabolism; and more specifically, mycolic acid recycling. 9 In a previous study, we showed that a macrophage infection by a wild-type M. tuberculosis H37Rv strain resulted in the differential transcription of a large number of genes, by the macrophage, as early as 15 min post-infection, whereas the deletion of the Mce1 protein complex from the M. tuberculosis H37Rv strain, (M. tuberculosis D-mce1 H37Rv) delayed the uptake of the bacteria into the host macrophage, in addition to inducing an antiinflammatory response by 4 h post-infection. 10 For the current manuscript, the focus was shifted to genes showing sustained effects.…”
Section: Introductionmentioning
confidence: 99%